MAJOR TECHNIQUES OF ERROR CORRECTION IN ELT (Web of Discoveries: Journal of Analysis and Inventions, 2023)
The article is intended to discuss types of error correction and main principles of it in order to improve learners knowledge in ELT classroom. , Error correction is a way to develop competence of language learners in a second or foreign language. It can be utilized for attaining knowledge of a second or foreign language, and in learning the language’s rules.